A CORRELATIONAL STUDY BETWEEN PRODUCT INNOVATION, PRICE, PURCHASE INTENTION, AND PURCHASING DECISIONS AT RANTO KAYU FURNITURE IN RANTAUPRAPAT - Adelia Ningrum; Siti Lam’ah; Daslan Simanjuntak (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the effect of product innovation and price on purchasing decisions, with purchase intention as an intervening variable among consumers of Ranto Kayu Furniture in Rantauprapat. This research employs a quantitative approach with an associative research design. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling technique. Data analysis was conducted using path analysis and the Sobel test to examine the mediating effect. The results indicate that product innovation and price have a positive and significant effect on purchase intention. Furthermore, product innovation, price, and purchase intention also have a positive and significant effect on purchasing decisions. Purchase intention is found to have the most dominant influence in driving consumer purchasing decisions. The Sobel test results confirm that purchase intention acts as a significant intervening variable in the relationship between product innovation and price on purchasing decisions. Therefore, improving product innovation and setting appropriate pricing strategies can enhance consumers’ purchase intention, which in turn increases purchasing decisions.